STUDY ON THE CHEMICAL CONSTITUENTS OF THE ESSENTIAL OIL FROM NYCTANTHES ARBOR-TRISTIS AND ITS MOLECULAR DOCKING STUDIES - KARTHICK V; VENKATAREDDY G; DHARANI J; RAVI S (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objectives of this study were to determine the chemical composition of the essential oil obtained from the flowers of Nyctanthes arbor-tristis (NAT) and to carryout molecular docking studies against three bacterial proteins to study the mechanism of the antibacterial activity. Methods: The essential oil was obtained from the flowers of NAT by hydrodistillation and the chemical composition was determined by gas chromatography–mass spectrometry analysis. Docking study was carried out for 14 compounds identified from NAT against three bacterial proteins 1UAG, 3TYE, and 3UDI. Results: Fourteen compounds were identified in the essential oil. 1-octanol (74.81%) is the predominant compound followed by phytol (6.80%), bis (2-ethylhexyl) phthalate (5.88%), and eucarvone (4.23%). Many compounds are similar to that of the essential oil from jasmine. Among the 14 compounds identified, 7,9-di-tert-butyl-1-oxaspiro (4,5) deca-6,9-diene-2,8-dione interacted well with 1UAG and 3TYE and showed binding scores of −8.9 and −7.2 K Cal/mol, respectively, involving hydrophilic and hydrophobic interactions. With the protein 3UDI, the compound eucarvone exhibited a binding score of −7.1 K Cal/mol. Conclusion: The similarities between the essential oil constituents of flowers the two plants NAT and jasmine. Therefore, it could be concluded that NAT flowers of Coimbatore are a good source of fragrance for cosmetic industry and as an antibacterial agent.